A clinical case of thrombotic syndrome in a patient with chronic kidney disease in the terminal stage - Rudenko, Oleksandra; Karpenko, Olena; Paliienko, Igor; Yerokhovych, Victoria (The Ukrainian Scientific Medical Youth Journal, 2025)
thrombotic syndrome is a frequent problem in patients with kidney damage, especially in the terminal stage, when the issue of vascular access for the hemodialysis procedure is extremely relevant. The clinical case presented by us with repeated thrombosis of an arteriovenous fistula demonstrates the algorithm of diagnostic search for the causes of thrombotic syndrome. The purpose of the work is to draw the attention of doctors to modern diagnostic tests for thrombotic syndrome with the help of genetic tests, to report a clinical case of vascular access thrombosis in a patient with chronic kidney disease in the terminal stage against the background of a combination of mutations in the genes of the hemostasis system and an increase in blood homocysteine.